2012
DOI: 10.1503/cmaj.109-4195
|View full text |Cite
|
Sign up to set email alerts
|

Arm-twisting medical schools for core geriatric training

Abstract: A survey of the geriatrics content included in undergraduate and postgraduate curricula indicated that very few institutions bolstered such instruction over a four-year period ending in 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A need for mandates from accreditation bodies and professional regulators was identified by respondents. This approach would be challenging because Canadian accreditation organizations do not typically prescribe content (Monette & Hill, 2012) and educators are expected to prepare generalist practitioners. However, Canadian family medicine education standards are more prescriptive about geriatric content (The College of Family Physicians of Canada, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A need for mandates from accreditation bodies and professional regulators was identified by respondents. This approach would be challenging because Canadian accreditation organizations do not typically prescribe content (Monette & Hill, 2012) and educators are expected to prepare generalist practitioners. However, Canadian family medicine education standards are more prescriptive about geriatric content (The College of Family Physicians of Canada, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of 2005 and 2008 Canadian medical curricula found that geriatrics content increased in some undergraduate programs and decreased in others, and there was a decline in programs requiring geriatrics in senior undergraduate clinical practice (Gordon, 2011). Achieving curricular change in medicine in Canada has been referred to as a process of “arm twisting” (Monette & Hill, 2012, p. E515). Research indicates that support is often necessary to have change take hold and be sustained (Rogers, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Few physicians are joining this specialty in either country, 5 and initiatives to bolster training in geriatrics for undergraduate medical students in North America have met limited success. 7 As a result, there is a significant shortage of physicians caring for older adults. 8 Primary care physicians can care for the vast majority of elderly adults, but recent evidence indicates that "higher quality of care for general medical (e.g., hypertension, diabetes) conditions and geriatric conditions is associated with improved survival among community dwelling older adults," 9 and evidence indicates that detection and care of geriatric syndromes by healthcare providers is less optimal than the care provided for general medical conditions.…”
Section: Training Of Specialized Geriatric Physicians To Meet the Neementioning
confidence: 99%